2020
DOI: 10.1016/j.artd.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A Vertical Measurement System to Predict the Change in Leg Length in Total Hip Arthroplasty

Abstract: The management of leg lengths in total hip arthroplasty continues to challenge orthopaedic surgeons. The aim of this study is to test the reliability of a measuring device used to measure the resected femoral head and how the resulting intra operatively calculated change in leg length compares to the radiographically measured change in leg length. Four orthopaedic surgeons measured 20 femoral heads and the intra class coefficients of the raters were between 0.955 and 0.990 with a mean difference less 1 mm, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The mechanical failure rate was 9 % (5 hips). 5,8,9 In this case we demonstrated that a successful hip replacement can be achieved despite altered anatomy secondary to developmental changes. Clearly the abductor and external rotator muscle were atrophic, scarred, and weak.…”
mentioning
confidence: 63%
“…The mechanical failure rate was 9 % (5 hips). 5,8,9 In this case we demonstrated that a successful hip replacement can be achieved despite altered anatomy secondary to developmental changes. Clearly the abductor and external rotator muscle were atrophic, scarred, and weak.…”
mentioning
confidence: 63%
“…The freehand technique is a widely used technique, but it reveals great interobserver and intraobserver variability ( 6 ). Preoperative templates are also widely used, and digital templates have emerged to make the operation more convenient and the results more accurate ( 7 , 8 ). But studies have shown that in up to 60% of the cases, the preoperative template cannot accurately predict the correct size of the implant ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…LLD can be a cause of patient dissatisfaction because of ipsilateral gait disorder, knee pain, back pain and implant failure associated with inferior clinical outcomes [ 1 6 ]. Several methods have been reported for adjusting and equalizing leg length after THA [ 3 , 7 12 ]. As one of these methods, use of computer navigation in THA has been increasing over the last decade.…”
Section: Introductionmentioning
confidence: 99%